2012
DOI: 10.1111/j.1365-2702.2012.04189.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Struggling to be an insider’: a phenomenological design of new nurses’ transition

Abstract: Aims and objectives.  To obtain a comprehensive understanding of the transition process of new nurses in Taiwan. Background.  The transition period for new nurses can be a daunting and traumatic experience. The large number of newly graduated Taiwanese nurses who resign from their jobs within three months indicates that this process can be complicated. However, the problems associated with the experiences of new nurses have not yet been recognised. Design.  We adopted a phenomenological design using focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…The statement “nurses eat their young” was used to describe the bullying behaviour and hierarchical culture prevalent in the nursing profession (Pellico et al, ). In western culture, the horizontal violence and bullying is considered “toxic”; however, in Taiwan, it is justified as part of necessary training to improve the new graduates' abilities (Lee et al, ). In another Taiwanese study, Feng and Tsai () found that this exposure to horizontal violence can become endemic, enshrined in an old Chinese proverb, “a daughter‐in‐law who suffers will one day became a mother in‐law,” inferring that those who have suffered may one day become the perpetrators (Feng & Tsai, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statement “nurses eat their young” was used to describe the bullying behaviour and hierarchical culture prevalent in the nursing profession (Pellico et al, ). In western culture, the horizontal violence and bullying is considered “toxic”; however, in Taiwan, it is justified as part of necessary training to improve the new graduates' abilities (Lee et al, ). In another Taiwanese study, Feng and Tsai () found that this exposure to horizontal violence can become endemic, enshrined in an old Chinese proverb, “a daughter‐in‐law who suffers will one day became a mother in‐law,” inferring that those who have suffered may one day become the perpetrators (Feng & Tsai, ).…”
Section: Resultsmentioning
confidence: 99%
“…They should feel safe to ask questions as their competence develops (Ashton, 2015;Brewington, 2013); however, it was common for new graduate nurses to feel unsupported and undervalued (Brewington, 2013;Clark & Springer, 2012;Fink et al, 2008;Kumaran & Carney, 2014;Parker, Giles, Lantry, & McMillan, 2014;Pellico et al, 2009). Horizontal violence towards new graduate nurses is reported in the literature (Brewington, 2013;Feng & Tsai, 2012;Kumaran & Carney, 2014;Lee, Hsu, Li, & Sloan, 2013;Pellico et al, 2009). The statement "nurses eat their young" was used to describe the bullying behaviour and hierarchical culture prevalent in the nursing profession (Pellico et al, 2009).…”
Section: Professional Factorsmentioning
confidence: 99%
“…Second, this study showed a profound influence by the Chinese cultural values, which is characterised as assimilating to the system's culture and seeking harmony, following the power hierarchy and obedience to authority (Delury, ; Farh & Cheng, ; Kim & Oh, ; Lee, Hsu, Li, & Sloan, ). These intraconnected cultural values work interactively behind the scenes of Chinese evidence‐based nursing practice (Cheng et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…The impact of demographic factors (age, years in nursing, previous experience) and situational contributors (location of practice, type of work, access to supports) in influencing transition experiences have been previously identified across different workplaces (Bridges, ; Burns et al., ; Gohery & Meaney, ) and amongst new graduates (Lee, Hsu, Li, & Sloan, ; Missen, McKenna, & Beauchamp, ). In our study, age and years in nursing did not significantly impact on the transition experience.…”
Section: Discussionmentioning
confidence: 99%